Geopolitics of the South China Sea during the Covid-19 Pandemic: Indonesia’s National Interest and Geostrategy in the North Natuna Sea - Azmi, Mohammad Fazrulzaman (Politicon : Jurnal Ilmu Politik, 2023)
The Problem of territorial disputes in the South China Sea have long occurred in the dynamics of Indo-Pacific international politics. However, it is interesting that during the Covid-19 Pandemic situation, the conflict between Indonesia and China is increasingly accompanied by the involvement of the United States and Russia in the region. This essay aims to describe Indonesia’s national and geostrategic interests in the South China Sea conflicts region. This study uses qualitative methods, then data is collected using interviews and documentation. The results of this study found that Indonesia is interested in maintaining the sovereignty and economic potential in the North Natuna Sea. Indonesia is increasing patrols and military cooperation with the United States as a way to show sovereignty, even though China also influences the Indonesian economy, especially in investment. In addition, Indonesia is cooperating with Russia in exploring and exploiting oil and natural gas in the North Natuna Sea region. This military and business cooperation have become Indonesia’s geostrategy in counteracting China’s intervention in the North Natuna Sea region. The geostrategic implications strengthen Indonesia’s position in regional politics, especially related to defending territorial sovereignty from the threat of other countries.